2014
DOI: 10.1007/s11302-014-9437-0
|View full text |Cite
|
Sign up to set email alerts
|

Rat submandibular glands secrete nanovesicles with NTPDase and 5′-nucleotidase activities

Abstract: Extracellular nucleotides modulate a wide number of biological processes such as neurotransmission, platelet aggregation, muscle contraction, and epithelial secretion acting by the purinergic pathway. Nucleotidases as NTPDases and ecto-5′-nucleotidase are membraneanchored proteins that regulate extracellular nucleotide concentrations. In a previous work, we have partially characterized an NTPDase-like activity expressed by rat submandibular gland microsomes, giving rise to the hypothesis that membrane NTPDases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We also found NTPDase2 protein in Capan-1 cells, as well as secreted extracellular enzyme detected in a particulate fraction, which suggests microvesicular secretion. Such microvesicular secretion of ecto-nucleotidases has been proposed also for the rat pancreas and submandibular glands [14,73]. Overall, it appears that pancreatic ducts express ectoenzymes somewhat different to acini and to pancreatic juice arising from stimulation of acinar by cholecystokinin.…”
Section: Discussionmentioning
confidence: 61%
“…We also found NTPDase2 protein in Capan-1 cells, as well as secreted extracellular enzyme detected in a particulate fraction, which suggests microvesicular secretion. Such microvesicular secretion of ecto-nucleotidases has been proposed also for the rat pancreas and submandibular glands [14,73]. Overall, it appears that pancreatic ducts express ectoenzymes somewhat different to acini and to pancreatic juice arising from stimulation of acinar by cholecystokinin.…”
Section: Discussionmentioning
confidence: 61%
“…It was previously demonstrated that e-5′NT and NTPDase1, 2 and 3, but not NTPDase8, are expressed in rat SMG, mostly associated to microsomes [ 78 ]. Subsequently, this activity was predominantly attributed to substrate inactivation by rat and human NTPDase2 [ 79 ]. Furthermore, it has been reported that nanovesicles contained in rat saliva have the ability to hydrolyze ATP.…”
Section: Purinergic Signaling In the Salivary Glandsmentioning
confidence: 99%